Operasional Produk Investasi Emas Pada Pegadaian Syariah Ditinjau Dari Prinsip Ekonomi Islam - Purnamasari Purnamasari; Kurniaty Kurniaty; Purnama Rozak (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Investment is one of the important instruments as collateral in the future for every human being. Pawnshop institutions are now growing rapidly can be an alternative for customers whowish to invest. The purpose of this study was to determine oprasional Gold Investment in Islamic pawnshop-related goals, mechanisms, customer requirements the applicant, term, collateral, benefits and fees charged to customers in terms of the applicant’s gold investment principles of Islamic economy in the form of fatwas and outlook muamalah fiqh. This study uses field research by visiting the direct object of study to obtain the required files through interviews, observation on operationality of Gold Investment. While the analysis is used to process the data that has been obtained is descriptive analysis to produce results. Results from this study is that Gold Investment to buy mortgage scheme on Islamic Pawnshop or Sharia Pawnshop has not fully correspond to some Fiqh Fatwa and Economic Islam Principles, that the clarity of the goods at the contract, which contains the value of speculative investments.